Kloning Gen pcbC dari Penicillium chrysogenum ke dalam Plasmid pPICZA untuk Pengembangan Produksi Penisilin G - Wiharyani, Risma; Hardianto, Dudi; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto (Bioma : Berkala Ilmiah Biologi, 2014)
Availability of drugs in Indonesia is still limited by the high prices of drugs due to on the imported raw materials that reaches 95%. Developing antibiotic raw materials can be achieved by increasing of penicillin G production, which is the raw material for the formation of semisynthetic penicillin derivatives through the production of 6-aminopenisillanic acid (6-APA). One of the important enzyme in the penicillin G biosynthesis is Isopenisilin N Synthase (IPNS) that encodes by pcbC gene on Penicillium chrysogenum. This study aimed to obtain a recombinant of pcbC gene fragments that is inserted into pPICZA plasmid. Amplification of pcbC gene used pcbC-F and pcbC-R primers. The pcbC gene fragment was inserted into pPICZA vector and then transformed into TOP 10 F’. The results showed that the recombinant of the pcbC gene fragment from P. chrysogenum has been obtained. Analysis of DNA sequences using the BLAST program showed that the pcbC gene fragment has high homology (99%) with the pcbC gene from P. chrysogenum Wisconsin 54-1255 and P. chrysogenum AS-P-78 which encodes IPNS Keywords: pcbC Gene, Penicillium chrysogenum, cloning, penicillin G